Determinação da influência do contorno de grão na medida de difusividade térmica em cerâmicas supercondutoras YBa2Cu3O7- - Rouver, Anderson do Nascimento (2013)
YBa2Cu3O7− polycrystalline samples were prepared by technique of solid vapor-reaction with the aim of studying the thermal diffusivity. Three samples were prepared from the oxides of copper and yttrium and barium carbonate. After mixing, each sample was identically compacted and subjected to a uniaxial pressure of 1 ton. Then the samples were heat treated at different levels: sample A was sintered at 970∘C and oxygen to 400∘C; sample B was treated at 950∘C and for sample C the level was 970∘C. Each sample remained at these levels for 24 hours. These samples were characterized by XRD, ac magnetic susceptibility and scanning electron microscopy. All results indicate that sample A did not form the superconducting phase. Samples B and C have equal to 91,8 K and 91,3 K respectively. The SEM image analysis indicated that the samples have different sizes of the junctions, and for sample C was found highest. EDS analyzes indicated the concentration of ions in the center of the grain and edge grain for each sample. In the case of sample A, it was confirmed that the superconducting phase has not been established. Finally, we performed measurements of thermal diffusivity by the flash method. Thermal diffusivity measurements indicated that sample C has higher thermal diffusivity than sample B. However, due to experimental limitations, the uncertainties are relatively high.